A study of the effectiveness of training program in Bank Kerjasama Rakyat Malaysia Berhad based on employees' perceptions / Intan Nur Hafizah Mat Nawi - Mat Nawi, Intan Nur Hafizah (2016)
The purpose of this study is to identify the effectiveness of training program in Bank Kerjasama Rakyat Malaysia Berhad. This study investigates the most use of training techniques either of information distribution technique, simulation technique or on-the-job training technique. The questionnaires had been distributed randomly to the employees in Bank Kerjasama Rakyat Malaysia Berhad. The population for this study was 110, and sample size that being used based on Krejcie & Morgan table from a given population was 86 respondents. After collected the questionnaires from the respondents, the data had been analyzed by using Statistical Packages for the Social Sciences (SPSS) version 20 to get the results. Based on the findings, most of respondents choose on-the-job training technique as the mostly training program practiced in Bank Kerjasama Rakyat Malaysia Berhad. The findings also show that the level of the effectiveness of training program is good. The researcher suggested that simulation training technique also should be used to train employees by using advance technology besides it can improve the employees' skills and knowledge.